The impact of soybean expansion on mammal and bird, in the Balsas region, north Brasilian Cerrado - Barreto, Larissa; Van Eupen, Michel; Kok, Kasper; Jongman, Rob H. G.; Ribeiro, Milton C. [UNESP]; Veldkamp, Antonie; Hass, Adriani; Oliveira, Tadeu G. (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
In order to analyse the impact of land use change, it is particularly important to know how organisms use resources distributed across a heterogeneous landscape. The main objective of this study is to analyse the potential impact of land use change on bird and mammal fauna, by using a coupled model approach. The CLUE (Conversion of Land Use and its Effects) model has been applied to obtain the spatial pattern of land use change for a scenario with soybean expansion in the Cerrado of Maranhao State in Brazil. These land use change maps were used as the input for the LEDESS (Landscape Ecological Decision and Evaluation Support System) model to evaluate the impact of habitat fragmentation on mammal and bird species. The scenarios demonstrated that high quality habitat for all studied species will be lost in the future when current trends in agricultural expansion continue, but these changes will have species-specific impacts. The most relevant ecological impact under the explored scenarios was habitat fragmentation expressed by the increase the number of habitat clusters. The coupled model approach of LEDESS and CLUE made it possible to project the spatial impact of soybean expansion on habitat dynamics in the studied region. This model approach can help to design effective ecological infrastructure to facilitate species survival and to implement an effective habitat network in the Balsas region. Published by Elsevier GmbH.
Keywords: Land use change; Species modeling; CLUE; LEDESS; Maranhao; Biodiversity conservation